Comparative Analysis of Practices of Child Benefits in EU Member States - Uğur Emre Bektaş; Selim Dağlıoğlu (Selçuk Üniversitesi Sosyal Bilimler Meslek Yüksekokulu Dergisi)
According to the ILO Convention No. 102, family benefits are a social security branch established to compensate for the increase in the expenditure of those protected due to the expenses necessary for the care of the children, they are responsible for, and to protect the level of life they have reached before the child's existence. Periodic payments made to those who take care of the child within the scope of the family benefits social security branch are generally called child benefits. Child benefit is the most basic and common type of benefit provided under the family benefits social security branch. It is possible to find child benefits in all countries where there is an institutional family benefits social security branch. Child benefit can make positive contributions in many such areas as increasing the fertility and population of the country, reducing poverty, preventing child poverty and extending the country's welfare level to the whole society. In this respect, countries develop different child benefit practices by developing different benefit conditions depending on their population policies and economic development levels. In this study, current practices in EU member countries are examined on the basis of minimum standards of child benefits under the Convention No. 102 and a comparative analysis of these practices is presented. As a result of the study, it has been seen that all parents residing in EU member countries have the opportunity to benefit from child benefits for their children residing in these countries, and child benefits are provided without premium except Austria and France.